2021
DOI: 10.1200/jco.20.03609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oncology Hospital at Home: Unplanned Health Care Utilization and Costs in the Huntsman at Home Real-World Trial

Abstract: PURPOSE Patients with cancer experience high rates of morbidity and unplanned health care utilization and may benefit from new models of care. We evaluated an adult oncology hospital at home program's rate of unplanned hospitalizations and health care costs and secondarily, emergency department (ED) use, length of hospital stays, and intensive care unit (ICU) admissions during the 30 days after enrollment. METHODS We conducted a prospective, nonrandomized, real-world cohort comparison of 367 hospitalized patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Data collected from wearable and nonwearable connected devices have been shown to correlate with clinically meaningful outcomes such as treatment toxicity and self-rated quality of life 14 . A recent prospective trial also showed that an intensive home hospital program for cancer patients reduced unplanned admissions and emergency room visits and substantially lowered the costs of care 85 …”
Section: Virtual Care In Oncologymentioning
confidence: 99%
See 2 more Smart Citations
“…Data collected from wearable and nonwearable connected devices have been shown to correlate with clinically meaningful outcomes such as treatment toxicity and self-rated quality of life 14 . A recent prospective trial also showed that an intensive home hospital program for cancer patients reduced unplanned admissions and emergency room visits and substantially lowered the costs of care 85 …”
Section: Virtual Care In Oncologymentioning
confidence: 99%
“…In addition, the evidence on how wider adoption of virtual care impacts overall health care utilization and costs remains uncertain. Some data suggest increased use of telehealth may prevent avoidable acute care encounters 83,85 . However, there remain concerns that telehealth may increase the overall number of visits.…”
Section: Virtual Care In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent trial found decreased cost and healthcare use among patients with cancer hospitalized at home. 54 , 55 Studies published 2 decades ago demonstrated that patients with neutropenic fever may be treated at home with antibiotics and close monitoring and thus may be great candidates for home hospitalization. 56 Furthermore, other illnesses may be amenable to home hospital care by further exploring the literature and innovating care protocols.…”
Section: What Is Home Hospital?mentioning
confidence: 99%
“…Hospital-at-home programs have been proposed as a model for integrating palliative care that would address patients' needs at home or provide alternatives to emergency department (ED) use and hospitalization. Mooney and colleagues conducted a prospective, nonrandomized, real-world cohort comparison of patients managed an oncology hospital at home program or standard of care [105]. The hospital at home intervention was associated with fewer unplanned hospitalizations, shorter hospital length of stay, and fewer ED visits.…”
Section: The Role Of Supportive Oncology and Palliative Care Servicesmentioning
confidence: 99%